FOCMS: An ultrafast optical clearing method with quantified analysis - Xu, Xiaobin; Zheng, Yameng; Xiao, Xiao; Wang, Zizheng; Lv, Jie; Wang, Yongjie; Zhang, Jianmin; Duan, Shumin; Si, Ke (Frontiers in Physics, 2022)
Optical clearing technology offers a prospective solution to improve the imaging depth and quality of optical microscopy, but there is still a lack of quantitative standards to accurately evaluate transparency effects so the composition and concentration of most reagents are not optimal. Here, we propose a transparency quantitative analysis method (TQAM) based on the tissue area recognition technique to achieve the high-throughput reagent concentration gradient screening. After optimizations of reagent composition, concentration, operation time and other parameters of the optical clearing, we develop a new ultrafast optical clearing method with quantified analysis (FOCMS) with excellent transparency effect, simple operation, improved imaging depth and quality, minor morphological change and outstanding fluorescence retention. Applied the FOCMS to an application of human brain tissue, significant differences are observed between glioma and normal human brain tissue, while these differences are difficult to be found without the assistance of FOCMS. Therefore, FOCMS shows great application potential in clinical diagnosis and treatment, pathological analysis and so on.